Topical Treatment with Bergamot Flavonoid-Based Gel in Post-Surgical Wounds after Hemorrhoidectomy: Preliminary Results - Cafaro, Dott. Danilo; Sturiale, Dott Alessandro; Stefania Sinicropi, Dottssa Maria; Onofrio, Dott. Luciano; Catalano, Alessia; Naldini, Prof. Gabriele (International Journal of Innovative Research in Medical Science, 2022)
Background: Haemorrhoidal Disease (HD) is a very diffuse anorectal condition that involves a large part of the population, both male and female of every age. Among the several procedures proposed to treat HD, conventional excisional surgery remains one of the most performed, it is characterized by important post-operative pain whose historical knowledge often scare the patients. The pain is mainly related to the anal wounds and the healing speed surely influence the post-operative course. The aim of this study was to evaluate the effect of using Benebeo Gel® on post-operative wound healing after open haemorrhoidectomy. Methods and Results: This was an observational prospective study conducted in the Proctological and Pelvic Floor Clinical Centre (PPFCC) of the University Hospital of Pisa. From April 2019 to January 2020 all the 175 patients aged between 18 and 75 undergone to open hemorrhoidectomy were enrolled. The post-operative follow-up was scheduled as follows: 7 day, 15 day, 22 days and 30 days after surgery. The primary end point was: time taken to get complete wound healing with a re-epithelized tissue. Secondary endpoints were: evaluate post-operative pain using VAS scale, bleeding, discharge and overall patients satisfaction about the procedure and the topical gel. All the patients were instructed to take topical gel by using the cannula provided with the product put it into the finger phalanx and then upon injured area twice a day (once in the morning after defecation and once before sleeping) for 25 days after. The administration of the product begins in 4th post-operative day. The mean post-operative pain at 7 days was 6±2, at 15 days 4±1 at 22 day 3 and at 30 days was 2±1. The mean time to get complete wound healing was 23±4 days. Conclusions: He present study aimed to evaluate the efficacy of a new topical gel mainly composed by bergamot-derived flavonoids and hyaluronic acid in patients treated with excisional hemorrhoidectomy. The results after 2 weeks of treatment seems to be promising with a very good clinical outcome and patient satisfaction within 1 month.